Interpretation of Double Tax Convention – a Still Controversial Topic - Mössner, Jörg Manfred (Challenges of Contemporary Tax Law: Jubilee Book Dedicated to Professor Włodzimierz Nykiel. Volume II, 2024)
The article deals with controversies regarding the interpretation of tax treaties based on Art. 3 Para. 2 of the OECD Model in relation to Vienna Convention on the Law of Treaties.